5-Lipoxygenase: Underappreciated Role of a Pro-Inflammatory Enzyme in Tumorigenesis - Steinhilber, Dieter; Fischer, Astrid S.; Metzner, Julia; Steinbrink, Svenja D.; Roos, Jessica; Ruthardt, Martin; Maier, Thorsten J. (Frontiers in Pharmacology, 2010)
Leukotrienes constitute a group of bioactive lipids generated by the 5-lipoxygenase (5-LO) pathway. An increasing body of evidence supports an acute role for 5-LO products already during the earliest stages of pancreatic, prostate, and colorectal carcinogenesis. Several pieces of experimental data form the basis for this hypothesis and suggest a correlation between 5-LO expression and tumor cell viability. First, several independent studies documented an overexpression of 5-LO in primary tumor cells as well as in established cancer cell lines. Second, addition of 5-LO products to cultured tumor cells also led to increased cell proliferation and activation of anti-apoptotic signaling pathways. 5-LO antisense technology approaches demonstrated impaired tumor cell growth due to reduction of 5-LO expression. Lastly, pharmacological inhibition of 5-LO potently suppressed tumor cell growth by inducing cell cycle arrest and triggering cell death via the intrinsic apoptotic pathway. However, the documented strong cytotoxic off-target effects of 5-LO inhibitors, in combination with the relatively high concentrations of 5-LO products needed to achieve mitogenic effects in cell culture assays, raise concern over the assignment of the cause, and question the relationship between 5-LO products and tumorigenesis.